Evaluation of Dental Arch Form Using 3D Dental Cast Scanning Technology - Adaškevičius, R.; Vasiliauskas, A. (Elektronika ir Elektrotechnika, 2009)
Aim of our study is to consider a possibility of using 3D models for evaluation of dental arch form and approximation of dental arch curvature by mathematical functions for treatment outcome planning. The three-dimensional scanner based on the laser triangulation method was used for scanning dental casts. Occlusal plane was determined using Principal Component Analysis method. Curve fitting of projected on plane anatomical points was carried out by utilizing β function calculated using orthometer data or distobuccal cusp tips of the first molars and the central incisors. For the analysis of the results correlation coefficient between fourth-order polynomial after treatment and β functions before treatment was calculated. The dental casts of 15 subjects were scanned and measured to test the reliability of method. 3D database from digital models is useful tool for analysis of developmental changes, diagnosis and treatment planning. Ill. 6, bibl. 9 (in English; summaries in English, Russian and Lithuanian).